Impelementasi Prinsip Nirlaba dalam Pengelolaan Yayasan: Antara Idealisme dan Realitas - Muhammad Fathan Haqiqi; Dewi Atriani; Muhammad Raihan (Belom Bahadat, 2026)
This study examines the effectiveness of non-profit principles in the management of foundations in Indonesia and the role of the state in ensuring the implementation of these provisions. Using a normative legal research method through a legislative approach, this study assesses the gap between normative regulations and field practices. The results of the analysis show that there are still irregularities in fund management due to weak transparency and accountability. These findings emphasize the need to strengthen oversight mechanisms, implement audits, and enforce good corporate governance so that the social objectives of foundations can be achieved.